Website-Based Running Sports Information System For Communities In North Sulawesi Using Extreme Programming Method - Inayah Syaban; Tohap Manurung; Aditya Kalua; Eric Alfonsius (Universitas Teknokrat Indonesia, 2025)
The community in North Sulawesi has shown a strong interest in running, as evidenced by the increasing number of running communities and events. However, the absence of an integrated platform that provides information about running routes, communities, and events has become a challenge for runners in accessing information efficiently. This study employs the Extreme Programming method and aims to develop a web-based information system that delivers comprehensive information related to running sports. The website features key components such as community profile pages, a running event calendar, and running route locations, complete with maps, route descriptions, track lengths, difficulty categories, photo galleries, and supporting facilities like toilets and resting spots. The displayed information is sourced from various local communities and is systematically organized to ensure easy access for the public. Additionally, the website includes a contact page that allows users to provide suggestions or feedback to the admin. It also features a function that enables event organizers to directly submit event data and running route locations into the system through the contact page. This system is expected to help the community access information more easily and increase participation in running activities throughout North Sulawesi